Zihinsel Yetersizlikten Etkilenmiş ve Normal Gelişen Çocuğa Sahip Ebeveynlerin Sıkıntıyı Tolere Etme, Depresyon, Anksiyete ve Stres Düzeyleri / The Distress Toleration Status, Depression, Anxiety and Stress Levels of Parents Who Have Normally Developed Children and Who Have Intellectual Disability Children - Akça, Fatih; Özyürek, Arzu (Journal of History Culture and Art Research, 2019)
Abstract Being a parent and especially being a parent of a child with an intellectual disability could lead to reactions such as anxiety, stress, or depression in parents. Individuals in these emotional states could exhibit several psychological and somatic symptoms, which can make it difficult for them to adapt to life. In order to cope with difficulties in life, the stress tolerance of individuals should be high. The present study aims to determine the differences between the distress toleration of parents who have children with typical development (TD) and with intellectual disorders (ID) children and their depression, anxiety and stress levels. The study was designed as a quantitative study. The quantitative study data was collected from 90 mothers and 90 fathers (n=180) who have children with ID and 92 mothers and 92 fathers (n=184) who have children with TD (total:364). The study data were collected with Distress Toleration Scale and the Depression Anxiety Stress Scale. Since the quantitative study data did not exhibit normal distribution based on the Shapiro-Wilk test, Mann Whitney U-Test was used. Thus, it was determined that acceptance of distress and coping with problem capacities of parents who have children with ID were lower when compared to parents who have children with TD. It was determined that parents who have children with ID could tolerate the distress less and had higher depression-anxiety-stress levels when compared to other parents who have children with TD. Öz Çocuk sahibi olmak ve özellikle de zihinsel yetersizlikten etkilenmiş çocuğa sahip olmak, ebeveynlerde anksiyete, stres veya depresyon tepkileri oluşturabilir. Bu duygu durumları, psikolojik ve bedensel pek çok belirti verebilir, bireylerin yaşama uyumlarını güçleştirebilir. Yaşanan güçlüklerle başa çıkabilmek için bireylerin sıkıntı toleranslarının yüksek olması gerekir. Bu çalışmada, zihinsel yetersizlikten etkilenmiş (ZYE) ve normal gelişim gösteren (NGG) çocuğa sahip ebeveynlerin sıkıntıyı tolere etme durumları ile depresyon, anksiyete ve stres düzeylerini belirlemek amaçlanmıştır. Çalışma nicel olarak tasarlanmıştır. Çalışmanın örneklemini ZYE çocuğa sahip 90 anne ve 90 baba (N=180) ve NGG çocuğa sahip 92 anne ve 92 baba (N=184) olmak üzere 364 ebeveyn oluşturmuştur. Verilerin toplanmasında Sıkıntıyı Tolere Etme Ölçeği ve Depresyon Anksiyete Stres Ölçeği kullanılmıştır. Verilerin analizinde yüzde ve frekans dağılımları alınmış, değerler normal dağılmadığından ölçek puanları arası farkın belirlenmesinde Mann Whitney-U Testi kullanılmıştır. Ölçek puanları arasındaki ilişkinin incelenmesinde korelasyon analizi kullanılmıştır. Sonuç olarak; ZYE çocuğa sahip ebeveynlerin NGG çocuğa sahip ebeveynlere göre depresyon, anksiyete ve stres düzeyinin daha yüksek olduğu, sıkıntıyı kabullenme ve sıkıntıyla baş etme kapasitelerinin daha düşük olduğu belirlenmiştir.